The Issue of the Choice of Qiraat in Zamakhshari and Abū Hayyān - Özbek, Ömer; Kahraman, Sena (Scientific Journal of Faculty of Theology, 2023)
The concept of ikhtiyār means choice and freedom of choice. Al Ikhtiyār, which has been dealt with in different fields with different dimensions, has been accepted as an important issue in the science of qiraat in the sense that one way of qiraat is considered as the main one or one of the ways of qiraat is prioritized over the other. The phenomenon of ikhtiyār stands out with its defining feature from the period of the Companions to the imams of qiraat and even to the scholars of the seventh century. This concept, which determines the working framework of qiraat scholars, is included in the lines and is used as a name in cornerstone works as well as in Kitâb al Ikhtiyâr and the like. Although the number is small, there are still studies on this issue today. Abū Ḥayyān, an Andalusian commentator, is an important scholarly figure who makes a choice between the non-mutawatir qiraats in his tafsīr. However, he does not make an option among the mutawatir qiraats and rejects such an option. Therefore, his view on the issue of ikhtiyār is important. The subject of this study is the evaluation of the phenomenon of old age, which is one of the leading issues of the science of qiraat, from the perspective of the commentator Abū Ḥayyān. The aim of research is to examine the phenomenon of old age, which expresses the selections made from the existing qiraat accumulation, from the perspective of a commentator. It will be tried to bring a different perspective to the issue with the comparisons made within the limits of the study. In this study, it is not aimed to deal with the issue of elders with its historical process and pause times, but it is aimed to present and briefly evaluate the issue within the framework of Zamakhshari and Abū Hayyān's views on the issue.